Disaster risk communication: attitudes of Serbian citizens - Cvetković, Vladimir M; Radovanović, Marko; Milašinović, Srđan (Sociološki pregled, 2022)
The objective of this research was to examine the citizens‘ attitudes to various factors influencing the implementation of effective disaster risk communication in the Republic of Serbia. In addition, the research aims to scientifically describe the predictors of successful disaster risk communication. Using an online survey questionnaire, based on the snowball principle, 243 respondents were surveyed during July 2021. The results of the multiple linear regression analysis used to assess the explanatory power of six selected variables (gender, age, education, marital status, employment, and income level) on the perception of disaster risk communication show that the most important predictors of risk awareness are income level and gender. The obtained results have multiple scientific and practical importance for the improvement of integrated disaster risk communication through the process of improved understanding of the demographic and socio-economic perspective of communication.
Keywords: disasters; risks; communication; factors; innovation; research